Peter Dickinson : words and music - Dickinson, Peter, 1934- (Cambridge EBA Collection, 2016)
Peter Dickinson has made an enduring contribution to British musical life, and his music has been regularly performed and recorded by leading musicians. His writings, brought together here for the first time, are equally noteworthy. Covering well over half a century, the subjects are fascinatingly varied. Apart from musical interests ranging from Charles Ives to John Cage, they touch on literature; and Dickinson's meetings with W.H. Auden and Philip Larkin are an intriguing insight that led to his Auden songs and the chamber work Larkin's Jazz. American themes are prominent in this collection. There are unique reviews of concert life in New York from 1959 to 1961; an account of the teaching programme at the Juilliard School of Music at that time; three studies of Ives; and featurescontaining original material on Copland, Thomson and Cage, all of whom Dickinson knew. Features on Erik Satie include the imaginary discussion marking his centenary in 1966. Dickinson also writes about his own music, providing an insight into what it was like being a British composer in the later twentieth century. Peter Dickinson was born in Lancashire in 1934 and now lives in Suffolk. His 80th birthday was marked by a whole variety of tributes, including concerts, articles, broadcasts and various interviews - some included in this book. PETER DICKINSON is a British composer andpianist as well as author and editor of Boydell/URP books on Berkeley, Copland, Cage, Barber and Berners. As a pianist, Dickinson had a twenty-five-year, international partnership with his sister, the mezzo Meriel Dickinson, for whom he wrote song cycles to poems of E.E. Cummings, Gregory Corso and Stevie Smith. He was a regular contributor to BBC Radio 3 and is widely read as a critic on the Gramophone. He is an Emeritus Professor of the Universities of Keele and London and is chair of the Bernarr Rainbow Trust, for which he has edited several books on music education.